Perlindungan Hukum Terhadap Eksploitasi Anak: Studi di Kelurahan Kota Rantauprapat, Kabupaten Labuhanbatu - Harahap, Syopwan Fadillah; Siregar, Muhammad Yusuf; Tampubolon, Wahyu Simon (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study explores how legal aspects play a role in protecting children from exploitation in Rantauprapat City, especially when faced with the reality of unhealthy parenting patterns and a wide economic gap. Using normative juridical methods and a qualitative sociological approach, it was found that economic exploitation of children is rife in the informal sector, such as selling crackers and tissues in cafes. The results of the study revealed that this action is often misinterpreted as a form of